THE OVERVIEW OF SCIENTIFIC ACHIEVEMENTS IN RESEARCHING OF DEGENERATIVE DISEASES OF THE SPINE IN SCIENTIFIC CENTER OF RECONSTRUCTIVE AND RESTORATIVE SURGERY SB RAMS FOR 10 YEARS - M. A. Makarova (Acta Biomedica Scientifica, 2013)
This article represents the result of 10 years work of scientific stuff going into researching of degenerative diseases of the spine. The new theoretical knowledge taken to the basis of new ways of diagnostics, forecasting and treatment was obtained. The introduction of suggested new technics of diagnostics, treatment and forecasting of pathologies of the spine let to improve results of treatment of patients with spinal stenosis, postoperative adhesion scar-epiduritis, herniated intervertebral discs, instability of the spinal motion segment. Finding out the regularities and mechanisms of multifactorial syndrome of instability was taken as the basis of working out by scientists pathogenically founded ways of correction of this syndrome. All new methods are patented and adopted by new technologies.